PENDEKATAN FRAMEWORK CODEIGNITER DENGAN METODE AGILE PADA SISTEM PENGGAJIAN (SIP-WEB) PT. GLOBAL PRINTPACK INDONESIA - Yesicha Audria; Isnan Budi Sahputro; Rendi Yusuf Alfiansyah; Andriansah Andriansah (INFOTECH journal, 2024)
PT. Global Printpack Indonesia is engaged in plastic factories located in Curug District, Tangerang Regency. The company has 280 employees. With the employee payroll data management system that is already running, it uses Microsoft Excel which is taken from the fingerprint attendance data recap. So that during the HRD payroll process, it takes longer to calculate salaries. Therefore, a computer-based payroll system was developed with a data import feature. The goal is to help simplify the process of recording overtime hours, monitoring employee attendance more efficiently. So HRD does not need to calculate manually. The data collection methods used in the preparation of the thesis are observation, interviews and literature studies and agile software development methods using the codeigniter 3 framework. The existence of this payroll system can make it easier for HRD to calculate salaries automatically to increase efficiency